Effects of a carbohydrate-, protein-, and ribose-containing repletion drink during 8 weeks of endurance training on aerobic capacity, endurance performance, and body composition - Cramer, J. T.; Housh, T. J.; Johnson, G. O.; Coburn, J. W.; Stout, J. R. (The Journal of Strength and Conditioning Research, 2012)
This study compared a carbohydrate-, protein-, and ribose-containing repletion drink vs. carbohydrates alone during 8 weeks of aerobic training. Thirty-two men (age, mean ± SD = 23 ± 3 years) performed tests for aerobic capacity (VO2peak), time to exhaustion (TTE) at 90% VO2peak, and percent body fat (%fat), and fat-free mass (FFM). Testing was conducted at pre-training (PRE), mid-training at 3 weeks (MID3), mid-training at 6 weeks (MID6), and post-training (POST). Cycle ergometry training was performed at 70% VO2peak for 1 hours per day, 5 days per week for 8 weeks. Participants were assigned to a test drink (TEST; 370 kcal, 76 g carbohydrate, 14 g protein, 2.2 g d-ribose; n = 15) or control drink (CON; 370 kcal, 93 g carbohydrate; n = 17) ingested immediately after training. Body weight (BW; 1.8% decrease CON; 1.3% decrease TEST from PRE to POST), %fat (5.5% decrease CON; 3.9% decrease TEST), and FFM (0.1% decrease CON; 0.6% decrease TEST) decreased (p = 0.05), whereas VO2peak (19.1% increase CON; 15.8% increase TEST) and TTE (239.1% increase CON; 377.3% increase TEST) increased (p = 0.05) throughout the 8 weeks of training. Percent decreases in %fat from PRE to MID3 and percent increases in FFM from PRE to MID3 and MID6 were greater (p = 0.05) for TEST than CON. Overall, even though the TEST drink did not augment BW, VO2peak, or TTE beyond carbohydrates alone, it did improve body composition (%fat and FFM) within the first 3-6 weeks of supplementation, which may be helpful for practitioners to understand how carbohydrate-protein recovery drinks can and cannot improve performance in their athletes.